1979
DOI: 10.1148/131.2.521
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Signatures with Dual-Energy Computed Tomography

Abstract: By providing information on two parameters, dual-energy computed tomography can offer clinically useful tissue signatures for metallic deposits (Ca) or injected iodine, as well as for different normal and abnormal types of brain parenchymal tissues and CSF. Cerebral CT was performed on 36 patients and tissue differences analyzed using Hounsfield notation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
74
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(76 citation statements)
references
References 0 publications
0
74
0
2
Order By: Relevance
“…Characterization of tissue and materials using dual-energy CT was first described in the late 1970s when CT technology was still in its infancy [1,2]. The technique was not adapted widely for clinical use except for bone densitometry [3] due to immature CT technology.…”
Section: Dual-energy Ct; Genitourinary Imaging; Iodine-subtraction Immentioning
confidence: 99%
“…Characterization of tissue and materials using dual-energy CT was first described in the late 1970s when CT technology was still in its infancy [1,2]. The technique was not adapted widely for clinical use except for bone densitometry [3] due to immature CT technology.…”
Section: Dual-energy Ct; Genitourinary Imaging; Iodine-subtraction Immentioning
confidence: 99%
“…It has also been recognized that iodine-based contrast media have unique X-ray absorption characteristics at different kV levels (Riederer and Mistretta 1977). Early experimental prototypes typically required the acquisition of two separate CT acquisitions at different kV levels with subsequent image coregistration, limiting clinical utility (Chiro et al 1979;Kalender et al 1986). Animal studies demonstrated that identifying and quantifying MI with dual-energy DE-MDCT is feasible (Zhang et al 2010;Deseive et al 2011).…”
Section: Dual Energy For Quantifying MImentioning
confidence: 99%
“…In 1979, Chiro et al, used 140 and 90 kVp computed tomography for brain scan. Their theoretical calculations and experimental studies indicated that dual-energy CT can provide clinically useful tissue signatures, not only for metallic deposits, calcification and bone or injected iodine, but was also helpful for the identification of different types of parenchyma tissues and body fluids (15 and subtraction method to enhance the qualitative imaging capabilities. They concluded that spectral dual-energy MDCT imaging of atherosclerotic coronary artery specimens using standard CT scanners will allow tissue characterization.…”
Section: Introductionmentioning
confidence: 99%